Perlindungan Hukum Bagi Pelaku Komiditi Pertanian Menghadapi Krisis Pangan Dengan Penguatan Anggaran - Saptaning Ruju Paminto; Azzahra Herawati; Bilkis Nabila; Nispi Aliyatunnisa; Resna Amelia Putri; Rizqi Ulmaliyah Alhaddi; Selsa Selviana; Siti Jenar Maharani; Widya Putri Maharani (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to understand and find out the factors behind the food crisis experienced by agricultural commodity farmers and the legal protection as well as the efforts made by the government to prevent food crises by strengthening the budget for agricultural commodity farmers. This research uses normative juridical research methods, research by tracing or reviewing and analyzing library materials or ready-to-use document materials. This research uses primary legal materials, namely legal materials originating from statutory regulations, such as Undang-Undang No.18 Tahun 2012 Tentang Ketahanan Pangan, Undang-Undang No. 19 Tahun 2013 Tentang Perlindungan dan Pemberdayaan Petani, Peraturan Pemerintah No. 17 Tahun 2015 Tentang Ketahanan Pangan dan Gizi, but also utilizing secondary legal materials such as relevant journals and books as well as tertiary legal materials in the form of data and facts from the internet. The results of the research show that this food crisis has a broad impact on Indonesian society, Indonesian people will experience soaring prices of basic commodities, hunger, dependence on imports, and affecting agricultural crop production. To overcome the food crisis, farmers must increase crop productivity in a sustainable way, such as using organic fertilizer, balanced fertilization, and using superior seeds. Apart from that, the government's efforts to handle the food crisis for agricultural commodity farmer include setting the basic price of food production and determining the government purchasing price (HPP).